2021
DOI: 10.1680/jbibn.20.00010
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of edible films from starch nanoparticles and chitosan

Abstract: This study aimed to investigate the properties of edible films derived from the biocomposites of starch nanoparticles (SNPs) and chitosan. Chitosan was prepared in concentrations of 1.5, 2.0 and 3.0 wt%. The SNPs and film properties were investigated. The functional group of SNPs and chitosan as the edible film was evaluated. Then, the morphological structure, mechanical properties, thermal behavior and contact angles of the obtained films were also investigated. The data were subjected to a general linear mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Singh and Kamlesh [23] also reported that when the concentrations of chitosan increased, the large size of the pebbles structure in the starch film fragmented to a smaller size, hence the smoother and more homogeneous structure. Similarly, Restu et al [11] also revealed that the SEM micrograph of the neat starch film has a large and rough granule structure. They also reported that when the starch matrix was incorporated with chitosan, the films exhibited a smoother surface than neat starch film due to the good intermolecular bonding between the chitosan and starch molecules.…”
Section: Surface Morphology Of the Filmsmentioning
confidence: 80%
See 3 more Smart Citations
“…Singh and Kamlesh [23] also reported that when the concentrations of chitosan increased, the large size of the pebbles structure in the starch film fragmented to a smaller size, hence the smoother and more homogeneous structure. Similarly, Restu et al [11] also revealed that the SEM micrograph of the neat starch film has a large and rough granule structure. They also reported that when the starch matrix was incorporated with chitosan, the films exhibited a smoother surface than neat starch film due to the good intermolecular bonding between the chitosan and starch molecules.…”
Section: Surface Morphology Of the Filmsmentioning
confidence: 80%
“…Among the many nanoparticles, chitosan nanoparticles (CNP) are natural materials that exhibit high antibacterial activity against a wide spectrum of pathogens [9,10], as well as antioxidant activity [11]. CNP has been used in food packaging, food coating, textiles, and other sectors [12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations